Optimalisasi Limbah Dapur Menjadi Pupuk Organik Cair: Pelatihan Warga di Desa Kodokan, Blora - Inanda, Izzah Aulia; Azizah, Tsaniyyah Nur; Hanoon, Khairuna Irby; Mubarok, Muhammad Fadhil; Pasaribu, Cindy Grasia; Jannah, Miftahul; Fatah, Apriyandi Kagendra; Zefrinardi, Aleyf Radyansach; Alexandi, Muhammad Findi (Jurnal Pusat Inovasi Masyarakat, 2025)
This community service activity was carried out to improve the knowledge and skills of Kodokan Village residents in processing kitchen waste into liquid organic fertilizer (POC) as an environmentally friendly alternative fertilizer. The main problems faced by the community are the high prevalence of burning household organic waste and the strong dependence on chemical fertilizers in land management. The program was implemented in two stages, namely (i) a counselling session explaining the concept, benefits, and production techniques of POC, and (ii) a direct demonstration so that participants are able to apply the process independently. A total of 17 participants actively took part in the activity on 13 July 2025. The evaluation results through pre-test and post-test showed a significant improvement in all indicators of participants’ understanding, with an average increase of more than 60 percentage points. After the activities, participants began to utilise vegetable scraps and fruit peels to produce POC independently at home and apply it to their home gardens. In addition to reducing organic waste, this program also contributes to reducing the use of chemical fertilizers, improving soil fertility, and creating environmentally based business opportunities through the production of POC as a potential local product. Therefore, this program serves as an initial step for sustainable waste management and for empowering the rural economy.